A Single-Center Experience with Minimally Invasive Transgastric ERCP in Patients with Previous Gastric Bypass: Lessons Learned and Technical Considerations. Issue 4 (April 2020) - Baimas-George, Maria; Passeri, Michael J.; Lyman, William B.; Dries, Andrew; Narang, Tarun; Deal, Stephen; Lewis, Jason; Chauhan, Shailendra; Martinie, John; Vrochides, Dionisios; Baker, Erin; Iannitti, David
As bariatric surgery increases, there is a growing population of patients with biliary obstruction and anatomy which precludes transoral access through endoscopic retrograde cholangiopancreatography (ERCP). Minimally invasive transgastric ERCP (TG-ERCP) offers a feasible alternative for the treatment. A retrospective review was performed of all patients who underwent laparoscopic or robotic-assisted TG-ERCP between 2010 and 2017. Chart abstraction collected demographics, procedural details, success rate, and postoperative outcomes. Forty patients were identified, of which 38 cases were performed laparoscopically and two robotically. Median operative time was 163 minutes, with an estimated blood loss of 50 cc. TG-ERCP was performed successfully in 36 cases (90%); sphincterotomy was completed in 35 patients (97%). Sixty per cent already had a cholecystectomy; in the remaining patients, it was performed concurrently. Major complications included stomach perforation (n = 1), pancreatitis (n = 3), and anemia requiring transfusion (n = 2). In patients with biliary obstruction and anatomy not suitable for ERCP, TG-ERCP can be performed in a minimally invasive fashion, with a high rate of technical success and low morbidity. We describe a stepwise, reproducible technique because it is an essential tool for the shared armamentarium of endoscopists and surgeons.